Mechanical characterization of 3D-printed silicone/epoxy hybrids. (2022) - Calais, Theo; Sebastian Joseph, Vincent; Jain, Snehal; Stalin, Thileepan; Valdivia Y Alvarado, Pablo
Abstract: A new family of materials made of chemically compatible silicone/epoxy hybrids was recently reported. By tuning the silicone/epoxy ratios, the elasticity of the hybrid could be finely tuned over five orders of magnitude. Processable by direct ink writing (DIW), an extrusion-based additive manufacturing technology, these materials displayed high interfacial toughness between different phases. In this study, the impact of two key parameters on the mechanical characterization of these hybrids was studied. First, the impact of reducing the tensile test specimen by a factor 3 from established ASTM standards was analyzed. It was found that reducing the sample dimensions does not significantly alter the mechanical properties, even though higher standard deviations were observed in the range of 5 to 15%, in particular for stiffer samples. Second, the impact of printing orientation was studied by comparing samples printed longitudinally and transversally to the tensile direction. Longitudinally printed samples exhibited higher stiffness properties of about 15% to 35% than transversally printed specimens (higher elastic modulus, lower elongation at break), while values between longitudinally printed and cast samples with same dimensions were comparable. These results show the possibility to reduce the sample dimensions when savings in processing time, costs, or materials are required, while processing materials by DIW impacts the mechanical properties.